Personalized Game-Based Content and Performance: A Pilot Study on a Digital Intervention for Children with ADHD - Seon-Chil Kim; Jeong-Heon Song; Na-Yeong Kong (Bioengineering)
Mobile-based digital interventions for children with attention-deficit hyperactivity disorder (ADHD) have been developed to alleviate their symptoms. When developing mobile game-based digital interventions for ADHD treatment, it is important to research how the emotional responses of the target audience members—based on flashy visuals or difficulty adjustments to motivate the user—affect their content manipulation ability. This study performed a correlation analysis to examine the impact of perceived difficulty and enjoyment (interest) on the performance of children diagnosed with ADHD while engaging in game-based digital content. Statistically significant differences were observed in the following variables based on the enjoyment level: correct rate (p = 0.0040), decision time (p = 0.0302), difficulty (p < 0.0001), and touch time (p = 0.0249). Considering difficulty level, statistically significant differences were observed for correct rate (p = 0.0011), decision time (p = 0.0158), and difficulty (p < 0.0001). Correlation analysis between the variables correct rate, decision time, difficulty, touch, time limit, and touch time based on enjoyment and difficulty did not reveal significant correlations. Therefore, for children with ADHD, digital interventions should focus on the therapeutic goals rather than on flashy visuals or difficulty adjustments aimed at enhancing interest. Based on these results, further research exploring how psychological states affect performance regarding digital content is necessary.